Incidence of surgical site infection in dogs undergoing soft tissue surgery: risk factors and economic impact. Issue 1 (5th October 2019) - Espinel‐Rupérez, Jorge; Martín‐Ríos, Maria Dolores; Salazar, Veronica; Baquero‐Artigao, Maria Rosario; Ortiz‐Díez, Gustavo
Abstract : Objectives: To determine (1) the incidence of surgical site infection (SSI) in patients undergoing soft tissue surgery at a veterinary teaching hospital and to study (2) and describe the main risk factors associated with SSI and (3) assess the economic impact of SSI. Design: Prospective cohort study. Setting: Veterinary teaching hospital. Participants: 184 dogs undergoing soft tissue surgery during a 12‐month period (October 2013 to September 2014). Primary outcome measure: Surgical site infection. Results: Out of the 184 patients analysed, SSI was diagnosed in 16 (8.7 per cent) patients, 13 (81.3 per cent) were classified as superficial incisional infection, 2 (12.5 per cent) as deep incisional infection and 1 (6.3 per cent) as organ/space infection. The administration of steroidal anti‐inflammatory drugs (P=0.028), preoperative hyperglycaemia (P=0.015), surgical times longer than 60 minutes (P=0.013), urinary catheterisation (P=0.037) and wrong use of the Elizabethan collar (P=0.025) were identified as risk factors. Total costs increased 74.4 per cent, with an increase in postsurgical costs of 142.2 per cent. Conclusions: The incidence of SSI was higher than the incidence reported in other published studies, although they were within expected ranges when a surveillance system was implemented. This incidence correlated with an increase in costs. Additionally new important risk factors for its development were detected.